Shell and Tube Heat Exchanger Design for Compressor Aftercooler with Delaware and Wills-Johnston Method - ZUHRI (NIM 13103113); Pembimbing: Dr. Ir. Halim Abdurrachim, SAIFUDIN
This final project presented a shell and tube heat exchanger design for compressor aftercooler. This design was done because the performance of aftercooler is not matching with company need, i.e. the fouling rate is too high, and both outlet temperature and outlet humidity are higher than required conditions. The working fluid that was used in this design is compressed air in shell side and cooling water in tube side. Heat transfer analysis used Delaware method and Wills-Johnston method. The calculation was applied to three chosen design alternative. The alternative design which was recommended to the company is the most inexpensive one. The detailed design on heat exchanger components was done based on Standards of Tubular Exchanger Manufacturers Association (TEMA). The heat exchanger type that was chosen is BEW type with one shell and two tube-passes. According to the chosen heat exchanger geometry, the fluid flow in shell side was analyzed by CFD software of FLUENT to find flow pattern and properties of this fluid. The calculation result of heat transfer using Delaware method and Wills-Johnston method is slightly different so these methods are suitable for heat transfer analysis in shell and tube heat exchanger. The result of fluid flow analysis with FLUENT is accurate enough or close to the theoretical analysis result. Therefore, it is important to analyze fluid flow along the shell in different surface of cross section with certain spacing to find completed conditions of fluid. More detailed design and analysis of heat exchanger is needed to have a heat exchanger design that can be fabricated and have good performance.